2004
DOI: 10.1016/s0306-4530(02)00136-1
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between testosterone supplementation and insulin-like growth factor-I levels and cognition in healthy older men

Abstract: Background. Our laboratory has previously reported that testosterone (T) administration to older men significantly improves cognitive function. This study examined potential changes in insulin-like growth factor (IGF) IGF-I, IGF-II and IGF-related binding proteins in response to T administration in older men and their relationship to cognitive functioning.Methods. Twenty-five healthy community dwelling volunteers, ranging in age from 50-80 years were randomized to receive weekly intra-muscular (i.m.) injection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 53 publications
0
26
0
Order By: Relevance
“…It is known that the number of GH receptors in the brain of rats declines with aging [37] and that IGF-1 potentiates acetylcholine release from the hippocampus. With aging there is a dramatic reduction of IGF-1 protein levels and receptor density in this structure [38, 39]. Changes in the cerebrospinal fluid concentration of the dopamine metabolite homovanillic acid are shown after GH treatment [4, 5, 40].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the number of GH receptors in the brain of rats declines with aging [37] and that IGF-1 potentiates acetylcholine release from the hippocampus. With aging there is a dramatic reduction of IGF-1 protein levels and receptor density in this structure [38, 39]. Changes in the cerebrospinal fluid concentration of the dopamine metabolite homovanillic acid are shown after GH treatment [4, 5, 40].…”
Section: Discussionmentioning
confidence: 99%
“…These studies showed significantly improved memory [62,64] and visuo-spatial function [62,63] in testosterone compared to placebo groups.…”
Section: Intervention Studiesmentioning
confidence: 96%
“…Twenty-five healthy volunteers (age 50-80) received weekly intra-muscular injections with either 100 mg testosterone or placebo for 6 weeks [23]. Serum IGF-I levels did not change in response to the testosterone treatment.…”
Section: Included Studies Concerning Igf-i and Cognitive Functioningmentioning
confidence: 99%